Mastering financial calculations : a step-by-step guide to the mathematics of financial market instruments - Steiner, Bob (Mastering Series., 2012)
Success in today's sophisticated financial markets depends on a firm understanding of key financial concepts and mathematical techniques. Mastering Financial Calculations explains them in a clear, comprehensive way - so even if your mathematical background is limited, you'll thoroughly grasp what you need to know. Mastering Financial Calculations starts by introducing the fundamentals of financial market arithmetic, including the core concepts of discounting, net present value, effective yields, and cash flow analysis. Next, walk step-by-step through the essential calculations and financial.